Medical Data Security Framework for Healthcare Systems - VenkatHarshithYadavG, S Nandini, Sushma patil, S Kalyan, Mrs. Chaithanya BN (International Journal of Advanced Science and Technology, 2020)
Data security and privacy has become a very essential thing in medical domain for preservationof healthcare data. Attacks of hackers can damage the patient’s data and may lead to disclosure to patient’s privacy.Medical data can usually be sensitive and it includes the entire patient’s biological condition. Therefore, a secure authentication framework is very important to offer health care data protection and privacy. Biometric access control of medical data will provide the necessary authentication and confidentiality. Biometrics has been used in recent years as an important tool for privacy protection.